2017
DOI: 10.1111/ceo.12888
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive glaucoma surgery as primary stand‐alone surgery for glaucoma

Abstract: Recently, many new devices and procedures have been developed to lower intraocular pressure in a less invasive and purportedly safer manner than traditional glaucoma surgery. These new devices might encourage an earlier transition to surgery and reduce the long-term commitment to topical glaucoma medications with their associated compliance and intolerance issues. Although often seen as an adjunct to cataract surgery, a growing body of evidence suggests that primary minimally invasive glaucoma surgery may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 31 publications
1
69
2
5
Order By: Relevance
“…Three eyes (12.5%) lost ≥2 lines of BCVA due to cataract progression after XEN‐45 stent implantation, likely secondary to the use of postoperative steroid eye drops. Despite the material of the XEN‐45 implant being soft and tissue‐conforming, implant exposure occurred in two eyes (8.3%) in our study and has also been reported previously …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Three eyes (12.5%) lost ≥2 lines of BCVA due to cataract progression after XEN‐45 stent implantation, likely secondary to the use of postoperative steroid eye drops. Despite the material of the XEN‐45 implant being soft and tissue‐conforming, implant exposure occurred in two eyes (8.3%) in our study and has also been reported previously …”
Section: Discussionsupporting
confidence: 85%
“…MIGS is typically characterized by a favourable safety profile, and this is the first report of serious and potentially sight‐threatening complications resulting from a MIGS device. Notably, these serious complications have not been reported after XEN‐45 implantation in eyes with primary open angle glaucoma . In comparison, ab interno trabeculectomy with the Trabectome was found to be effective for the treatment of uveitic glaucoma but was not associated with persistent hypotony or ocular infections .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, there has been a marked increase in MIGS uptake with Medicare data indicating an exponential increase in use over the last few years . Although MIGS is currently seen primarily as adjunct to cataract surgery, it is increasingly being considered as a viable initial treatment option …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, microincisional glaucoma surgery provides a safe IOP reduction with a short recovery time [7], has become an ideal option for early to moderate POAG [8].…”
Section: Introductionmentioning
confidence: 99%